Research Hotspots and Trends Analysis of Patellar Instability: A Bibliometric Analysis from 2001 to 2021 - Zheng, Zitian; Xu, Wennan; Xue, Qingyun (Frontiers in Surgery, 2022)
Abstract Background：Patellar instability is a common multifactorial disease in orthopedics, which seriously affects the quality of life. Because of the unified pathogeny, diagnosis and treatment, patellar instability has gradually attracted the interest of more scholars these years, resulting in an explosive growth in the research output. This study aims to summarize the knowledge structure and development trend in the field from the perspective of bibliometrics. Methods：The data of articles and reviews on patellar instability was extracted from the Web of Science database. The Microsoft Excel, R-bibliometrix, CiteSpace, VOSviewer, Pajek software are innovatively and comprehensively and used to scientifically analyze the data quantitatively and qualitatively. Results：Totally, 2155 papers were identified, mainly from North America, Western Europe and East Asia. Until December 31, 2021, the United States has contributed the most articles (1828) and the highest total citations (17931). Hospital for Special Surgery and professor Andrew A Amis are the most prolific institutions and the most influential authors respectively. Through the analysis of citations and keywords based on a large number of literatures, "medial patellofemoral ligament construction ", "tibial tubercle-trochlear groove (TT-TG) distance", "epidemiological prevalence", "multifactor analysis of etiology, clinical outcome and radiographic landmarks " were identified to be the most promising research directions. Conclusions：This is the first bibliometric study to comprehensively summarize the research trend and development of patellar instability. The result of our research provides the updated perspective for scholars to understand the key information in this field, and promote future research to a great extent.